PENGARUH MODE ERA VICTORIA TERHADAP MODE LOLITA STREET FASHION JEPANG - , RIZKY AYU GUSTARA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The title of this final project is âThe Impact of Victorian Fashion to Japanese Lolita Street Fashionâ. The subject of this final project is the comparison and explanation of several things taken from Victorian fashion that is still used in Lolita fashion and products that are affected by Lolita fashion. The writer chooses Lolita as the theme of this final project because Lolita fashion is unique with the embedded Victorian hoop skirt style on it. This final project uses literature method. The data are collected from books, literatures, articles and repots related to the problem being discussed. Explanation concerning with the comparison of Victorian fashion and Lolita fashion as well as the products influenced by Lolita fashion are presented in this final project. In addition, the writer also describes the Lolita fashion improvement history and types of Lolita fashion. The conclusion of this final project is there are differences between Victorian fashion and Lolita fashion on some part such as skirts, accessories, shoes, and so on. Some elements of Victorian fashion are still used in Lolita fashion. However several changes have been made. Not only fashion, there are many products that have been affected by Lolita mode including comic, movie, music, fashion brand, magazine and internet site.